THE EVOLUTION OF IRAN–SAUDI RELATIONS SINCE THE ESTABLISHMENT OF THE ISLAMIC REPUBLIC (Вісник: Міжнародні відносини, 2024)
Background. The Islamic Republic of Iran, whose political strategy in the Persian Gulf aims to promote the country's dominance in the region, inevitably faces the reaction of another influential regional rival – the Kingdom of Saudi Arabia. Since the declaration of the Islamic Republic, the relations between both countries have been characterized by unstable dynamics due to deep antagonism shaped by internal and external political factors. The purpose of the publication was to analyze the evolution of Iran–Saudi relations and identify key factors that determine the dynamics of relations and shape the causes of confrontation.Methods. The study utilized such general logical methods as analysis, deduction, induction and abstraction. Additionally, historical method, comparative method, modeling method, as well as methods of contextual and critical analysis were applied.Results. The study identified the interconnection of Iran's internal political dynamics with the nature of its relations with Saudi Arabia. Key conflict-generating factors included the nature of the political regimes in both countries, religious differences, the ideological discourse of the Islamic Republic, national identity, and the struggle for regional dominance. The intensification of the conflict is attributed to the peculiarities of regional alliances, the presence of the United States in the region, and active cooperation between Saudi Arabia and the USA, as well as Iran's ties with armed groups operating in the region and the nature of its nuclear program. Additionally, it was noted that the evolution of these relations is influenced by the United States and China.Conclusions. Based on the analysis of the research findings, it can be concluded that the relations between the Islamic Republic of Iran and the Kingdom of Saudi Arabia encompass a complex of issues due to the influence of a number of interconnected conflict-generating factors, which provoke confrontation. However, the resolution of this conflict may be possible with the involvement of non-regional actors.
Keywords: Islamic Republic of Iran, Kingdom of Saudi Arabia, Persian Gulf, regional security